LITERASI DAN HAK CIPTA PADA ERA KESULTANAN MAMLUK MESIR 1250–1517 M - Mafaza Silfi; Kholili Badriza (Batuthah: Jurnal Sejarah Padaban Islam, 2023)
This research analyzes copyrights owned or enjoyed by authors in the era of the Egyptian Mamluk Sultanate (648–923 AH/ 1250–1517 AD). Although the study focuses on the area and era of the Mamluk Sultanate, the idea of the integration of Islamic territories as one unified region (dār al-Islām) makes the results of this study have the potential to be drawn more broadly as a representative sample from various Islamic regions at that time. The main finding obtained from this research is that the massive literacy activities in the era of the Mamluk Sultanate gave rise to various unwritten agreements regarding an author's copyright among writers of that era. The emerging agreements tended to adapt to the conditions and spirit of the time, as the moral rights of writers in that era tended to be given more attention than the economic rights they had. The author's economic rights are almost completely limited to direct sales of the manuscripts he wrote/composed and rewards from their patrons. Meanwhile, copying manuscripts for personal and commercial purposes is done freely, almost without the author's permission. On the other hand, the second right, namely moral rights, whose embodiment is seen in the right of attribution and the right to safeguard the authenticity of manuscript content, seems to be considered more important by writers in this era. This tendency is because of the author's reputation and the potential influence (both in social, political, and religious aspects) that the writer can "enjoy" as an implication for the spread of the works he writes in various Islamic areas.